Energy performance and life cycle cost assessments of a photovoltaic/thermal assisted heat pump system - Cui, Yuanlong; Zhu, Jie; Zoras, Stamatis; Qiao, Yaning; Zhang, Xin (Elsevier, 2020)
A photovoltaic/thermal module assisted heat pump system is investigated in this paper, which provides electrical and thermal energy for a domestic building. In-depth evaluation on the system energy production is conducted based on the finite difference method for a long-term operating period. The 25 years’ system life cycle cost is assessed via the Monte Carlo simulation under the Feed-in Tariff (FiT) and Renewable Heat Incentive schemes, the annual energy savings, income and payback period (PBP) are compared for the FiT and Smart Export Guarantee (SEG) schemes. The technical analysis results illustrate that the system is able to fulfil the building thermal and electrical energy demands from April to October and from May to August, respectively, and the extra electricity of 229.47 kWh is fed into the grid. The economic assessment results clarify that the system achieves a net present value (NPV) of £38,990 and has a PBP of 4.15 years. Meanwhile, the economic sensitive analyses reveal that the high discount rate reduces the system NPV whereas the high investment cost causes a long PBP to realize the positive NPV. Compared with the SEG scheme, the FiT is the most cost-effective method for renewable electricity generation and has the shortest PBP
Keywords: Payback period; Net present value; Monte Carlo simulation; Thermal and electrical energy production; PV/T-HP system